KINERJA APARATUR SIPIL NEGARA DI BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA MANADO - Kumaat, Yunita Youlanda; Areros, William Agustinus; Pati, Agustinus Buche (Sam Ratulangi University, 2019)
This study aims to analyze and describe the performance of the State civil apparatus in the Manado CityRegional Tax and Retribution Management Agency. This research method uses descriptive qualitativemethod. Primary data obtained from interviews, observation and documentation. Secondary data is takenfrom documents, study libraries, articles of research results, and websites that support research. Researchinformants were determined using purposive sampling techniques, where informants were chosen basedon the researchers' judgment and judgment. The number of informants taken was 15 informantsconsisting of 1 person Inspectorate, leadership consisted of head of agency, head of division, head of subdivision and head of sub division as many as 6 people, community consisted of 6 taxpayers, PPAT / Notary1 person, headman of 1 person. The data obtained were analyzed descriptively through stages consistingof data reduction, data presentation and verification or conclusion drawing. This article argues that theleaders? ability need to improve compliance with SCA, by providing punishment and reward that buildsquality work. The quantity of work is influenced by the quality and utilization of available time. In thecase of time usage there is an SCA that works beyond the specified working hours to complete the work.Openness and mutual trust between SCA s in the Manado City Regional Tax and Retribution ManagementAgency by freeing the SCA s to express their aspirations without any restrictions as a form of cooperation.With the collaboration, SCA is also required to be able to take responsibility according to the job desk ofeach role.Kata Kunci: Performance; State Civil Apparatus; Regional Tax; Retribution; Management